Letter to Editor The Authors’ Reply - Mohammad Farajzadeh; Reza Ghanei Gheshlagh; Kourosh Sayehmiri (International Journal of Community Based Nursing and Midwifery, 2017)
DEAR EDITOR, I would like to thank for reviewing and criticizing the study entitle: “Quality of life in Iranian senior citizen: A systematic review and meta-analysis. With regard to the lack of using the Web of Science database and the lack of inclusion of some studies”, it is necessary to mention the following points: The growth and dispersion of studies have made it difficult to find up-to-date and relevant information.1 As no database covers all the health topics, it is recommended that multiple databases should be used for search.2 As the authors of “letter to editor” mentioned, the Web of Science database has not been used. This issue will be considered in future studies. Another point mentioned was neglecting the mean score for all the eight SF-36 domains. It should be noted that in reviewing the inclusion and exclusion criteria of the studies, the reviewers’ mentality may inevitably play a role and cause inclusion and exclusion criteria to be interpreted differently. The systematic review question determines which types of studies should be analyzed,3 and the purpose of this study was to estimate the overall score of the quality of life in the Iranian elderly (not its various dimensions). Therefore, the mean score for all the eight SF-36 domains has not been considered in the results. Regarding missing three articles in the review,4-6 considering the similarities between the overall mean score of the quality of life in these three studies and the overall score estimation in our study, adding these three studies makes no significant changes in the mean score. Furthermore, as in some studies in which the mean score of quality of life’s dimensions was not reported, the study of quality of life’s dimensions was not one of the objectives of this study.